Higher Tetanus Toxoid Immunity 2 Years After PsA-TT Introduction in Mali - Basta, Nicole E. (Clin Infect Dis, 2015)
Background. In 2010, mass vaccination with a then-new meningococcal A polysaccharide–tetanus toxoid protein conjugate vaccine (PsA-TT, or MenAfriVac) was undertaken in 1- to 29-year-olds in Bamako, Mali. Whether vaccination with PsA-TT effectively boosts tetanus immunity in a population with heterogeneous baseline tetanus immunity is not known. We assessed the impact of PsA-TT on tetanus toxoid (TT) immunity by quantifying age- and sex-specific immunity prior to and 2 years after introduction. Methods. Using a household-based, age-stratified design, we randomly selected participants for a prevaccination serological survey in 2010 and a postvaccination survey in 2012. TT immunoglobulin G (IgG) antibodies were quantified and geometric mean concentrations (GMCs) pre- and postvaccination among all age groups targeted for vaccination were compared. The probability of TT IgG levels ≥0.1 IU/mL (indicating short-term protection) and ≥1.0 IU/mL (indicating long-term protection) by age and sex was determined using logistic regression models. Results. Analysis of 793 prevaccination and 800 postvaccination sera indicated that while GMCs were low pre–PsA-TT, significantly higher GMCs in all age–sex strata were observed 2 years after PsA-TT introduction. The percentage with short-term immunity increased from 57.1% to 88.4% (31.3-point increase; 95% confidence interval [CI], 26.6–36.0;, P < .0001) and with long-term immunity increased from 20.0% to 58.5% (38.5-point increase; 95% CI, 33.7–43.3; P < .0001) pre- and postvaccination. Conclusions. Significantly higher TT immunity was observed among vaccine-targeted age groups up to 2 years after Mali's PsA-TT mass vaccination campaign. Our results, combined with evidence from clinical trials, strongly suggest that conjugate vaccines containing TT such as PsA-TT should be considered bivalent vaccines because of their ability to boost tetanus immunity.